Effect Of Topical Application Of Ozonated Olive Oil On The Number Of Lymfocite Cells In Male Wistar Rats With Periodontitis - Cindy Lestari; Aprilia Yuanita Anwaristi; Edi Karyadi; Ariyani Faizah (Sean Institute, 2023)
Periodontitis is an inflammation of the supporting tissues of the teeth caused by specific microorganisms or specific groups of microorganism which results in progressive destruction of the periodontal connective tissue and alveolar bone by forming pockets, recession or both. When there is inflammatory periodontitis, the lymphocyte cells increase. Lymphocytes are specific chronic inflammatory cells that become an immune response to the presence of an injury during inflammation. One of the treatments that support wound healing in periodontitis is Ozonated Olive Oil. Ozonated Olive Oil has a disinfectant ability that can suppress the growth of bacteria such as those contained in periodontitis. This study aims to determine the effect of topical application of Ozonated Olive Oil on the number of lymphocyte cells in male Wistar rats with periodontitis. The number of male wistar rats used was 24. Observation of lymphocyte cells was carried out using a light microscope with a magnification of 200x and counted manually by the observer.The results showed that the mean number of lymphocytes in the experimental group was 24±3.26599 and the negative control group was 48±5.65685. The result of the One-Way ANOVA data analysis is 0.000 (0<0.05). The conclusion of this study was that the use of 0.1 ml of Ozonated Olive Oil had an effect on the number of lymphocyte cells in male Wistar rats who had periodontitis.